(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Developinga talented workforce is essential to sustainable competitive advantage. Hence,a company that creates a talented workforce and implements suitable qualityservice programs is likely to succeed in a globally competitive economy (Kunduand Vora, 2004). Organizations are participants in talent wars in which rewardsgo to those companies who can attract, develop, use, and retain talent globally(Brake, 2005).